Location-Dependent Prediction of Dynamic Stability Limit for Peripheral Milling of Surfaces with Variable Curvatures - Baosheng Wang; Hongyan Hao; Mulan Wang; Junming Hou (Shock and Vibration)
The stability limit may change with the cutter’s location due to effect of curvature during the milling of a complex surface. The method for calculating the actual radial cutting depth is presented by accounting for the effects of curvature on the actual cutting parameters. The computed radial cutting depth is in turn used to determine the entrance/exit angles. Moreover, a milling system dynamic model is established based on the instantaneous milling force coefficients, and the stability limit is determined by means of the time-domain semidiscretization method. In addition, a location-dependent method for predicting the stability associated with the peripheral milling of a complex surface is put forward and simulation is carried out to generate a stability limit diagram. The effectiveness of the proposed method is verified through milling tests.